Dibenzoylmethane exerts metabolic activity through regulation of AMP-activated protein kinase (AMPK)-mediated glucose uptake and adipogenesis pathways. - Nami Kim; Hong Min Kim; Eun Soo Lee; Jung Ok Lee; Hye Jeong Lee; Soo Kyung Lee; Ji Wook Moon; Ji Hae Kim; Joong Kwan Kim; Su Jin Kim; Sun Hwa Park; Choon Hee Chung; et al. (PLoS ONE, 2015)
Dibenzoylmethane (DBM) has been shown to exert a variety of beneficial effects on human health. However, the mechanism of action is poorly understood. In this study, DBM increased phosphorylation of AMP-activated protein kinase (AMPK) and stimulated glucose uptake in a skeletal muscle cell line. Both knockdown of AMPK with siRNA and inhibition with AMPK inhibitor blocked DBM-induced glucose uptake. DBM increased the concentration of intracellular calcium and glucose uptake due to DBM was abolished by STO-609 (a calcium/calmodulin-dependent protein kinase inhibitor). DBM stimulated phosphorylation of p38 mitogen-activated protein kinase (p38 MAPK), which was blocked by pretreatment with compound C, an AMPK inhibitor. The expression of glucose transporter type 4 (GLUT4) was increased by DBM. The translocation of GLUT4 to the plasma membrane was also increased by DBM in AMPK dependently. In addition, DBM suppressed weight gain and prevented fat accumulation in the liver and abdomen in mice fed a high-fat diet. In pre-adipocyte cells, DBM decreased the activity of acetyl-CoA carboxylase (ACC), the rate-limiting enzyme of fatty acid synthesis. Expression of the adipogenic gene, fatty acid synthase (FAS), was suppressed by DBM in an AMPK-dependent manner. These results showed that the beneficial metabolic effects of DBM might be due to regulation of glucose uptake via AMPK in skeletal muscle and inhibition of adipogenesis in pre-adipocytes.